A novel framework for the economic and sustainability assessment of carbon capture and utilization technologies - Gasim Ibrahim (17032299) (2024)
This study presents a novel framework for assessing early-stage carbon capture and utilization (CCU) reactions. The introduced greenhouse gas abatement, sustainability, and economics framework (GASEF) assesses commercial viability by simultaneously analyzing a CCU technology's CO2 fixation potential with its economic potential. The developed framework combines a previously published CO2Fix parameter and the metric for inspecting reactants and sales (MISR) to estimate CO2 fixation and economic potentials. Both metrics can be estimated using limited information such as temperature, pressure, conversion, molecular weights, the heat of reaction, and the prices of the reactants and products of the CCU reaction. Results from this novel framework are demonstrated via case studies of notable CCU technologies, such as Dry Reforming of Methane and CO2 hydrogenation to methanol processes. Furthermore, the possible implications of providing CO2 subsidies for CCU processes for the gross CO2 input into these processes versus providing CO2 subsidies for the net CO2 fixation of the process is evaluated. In particular, the GASEF assessment on the DRM process showcased a potential for commercial viability even when the technology implementation requires additional investment of 0.1 $/kgCO2 (pertaining to low-concentration CO2 streams) due to carbon capture and sequestration efforts to achieve net-zero emissions. In the case of CO2 hydrogenation to methanol process, the GASEF assessment showcased the potential for commercial viability only at low CO2 credit (0.05 $/kgCO2); however, at values higher than this, the process becomes tenuous. These case studies provide a comprehensive demonstration of the use of the GASEF as a versatile tool to support rapid economics and sustainability evaluation of the new CCU technologies. Other Information Published in: Gas Science and Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jgsce.2024.205462